The Influence of a University’s Social Identity on NCAA Divisional Affiliation - Williams, Dylan P.; Seifried, Chad; Soebbing, Brian P. (Journal of Intercollegiate Sport, 2015)
Several scholars noted universities changing their intercollegiate athletic association are influenced by rival schools with similar social identities (Smith, 2011; Smith, Williams, Soebbing, & Washington, 2013; Washington, 2004, 2004–05; Weaver, 2010). Specifically, most of these studies reviewed institutions that were former members of the NAIA and moved to the NCAA since 1973, noting university officials affiliated with the NAIA considered the organization as a detriment to their own firm’s identity (Smith, 2011; Washington, 2004–05). Thus, many of these universities departed the NAIA to join the NCAA. However, NCAA affiliation requires institutions to review NCAA rules and regulations to determine which division best suit their respective school’s needs (i.e., Division II or III). Thus, the purpose of this study was to determine if a school’s many social identities influence the likelihood of movement from the NAIA to either Division II or Division III. The results from a logistic regression model showed schools located in the Southeast region of the United States, designated as an HBCU or a women’s college, considered a small or a large school according to the Carnegie Foundation or sponsor women’s basketball are more likely to leave the NAIA for Division II. Schools located in the Great Lakes region or affiliated with a Mainline Protestant denomination have higher tendencies to leave the NAIA for Division III. These results could assist the NAIA in the recruitment of new members and talk to current members possessing these identifies to create new mechanisms to retain their NAIA affiliation.